(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Geopolymer is an alumino-silicon gel consisting of tetrahedral SiO 4 and AlO 4 sections, polycondensed in a spatial structure as a result of the reaction between aluminosilicates and an alkaline activator.The report is a part of the complex research plan for geopolymers, in which information is given about the experimental results in the preparation of geopolymers from natural and man-made mineral components characteristic of Latvia (clay, sand, wood ash, brick waste).The aim of the study was to find out the dependence of the geopolymer formation process on the composition of the reacting components at constant exposure factors. Sodium alkali solution and sodium silicate was used in the experiments. The raw materials used are red and gray clay, sand, wood ash.The composition of the clay, ash and sand composition was changed with an interval of twenty percent. The obtained geopolymer samples were subjected to physical and technical tests. The compositions that are perspective in terms of properties in the studied modes of exposure have been determined.